The role of the knowledge economy in supporting sustainable development Applying to the vision of sustainable development 2030 - Abdul Qadir, Fatima Syed (The Arab Journal of Administration, 2025)
The study aims to present and analyze the role of the knowledge economy in supporting sustainable development, as the study showed that the knowledge economy has made a qualitative leap in economics by shifting from relying on traditional resources to focusing on knowledge resources, digital transformation and innovations that are characterized by their non-depletion with their use, as they are characterized by abundance. At the applied level, we note that the knowledge economy has a positive role in supporting sustainable development that guarantees the economic well-being of present and future generations. We note that the vision of sustainable development 2030 focuses on investing the resources of the knowledge economy with the support of international institutions, led by the United Nations and the IPO Organization for Invention and Innovation, and all countries of the world are witnessing plans and policies to implement the goals of Vision 2030.